DETERMINAN HARGA SAHAM PADA PERUSAHAAN ASING YANG ADA DI INDONESIA - Irni Yusnita; Winona Kumara Dewi (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2024)
This research aims to determine the effect of Return On Assets (ROA) and Return On Equity (ROE) on share prices in foreign companies in Indonesia for the period 2020 - 2023. The data used in this research is secondary data. This research uses quantitative associativity. This research uses multiple linear regression analysis methods and hypothesis testing with the t test and f test. The tool used is the SPSS version 22 program. The results of the research are (1) The first hypothesis, the results of partial testing (t test) between the return on assets variable (X1) and the stock price variable (Y) shows a t-count value of 2.148 and a significant value of 0.034 < 0.05, this shows that return on assets has a positive and significant effect on stock prices, so (H1) is accepted. (2) The second hypothesis, the results of the partial test (t test) between the Return On Equity variable (X2) and the share price variable (Y) shows a t-count value of 2.009 and a significant value of 0.047 < 0.05, it can be concluded that Return On Equity has a positive and significant effect on share prices, so (H2) is accepted. (3) The third hypothesis from the results of multiple linear regression coefficient analysis (F test) can be seen that the calculated F-value is 4.896 and the significant value is 0.009 < 0.05, so that the Ha hypothesis testing is accepted and Ho is rejected. The Ha hypothesis test concluded that return on assets, return on equity simultaneously (together) influence stock prices in foreign companies in Indonesia for the period 2020 - 2023. The SPSS output results can be seen that from the calculations the Adjusted R Square value is 0.061. , this shows that a large percentage of share prices can be explained by the independent variable return on assets, return on equity is 6.1% while the remaining 3.9% is influenced by other variables outside the model.